2019
DOI: 10.3390/app9194042
|View full text |Cite
|
Sign up to set email alerts
|

Human Neural Stem Cells Flown into Space Proliferate and Generate Young Neurons

Abstract: Here we demonstrate that human neural stem cells (NSCs) proliferate while in space and they express specific NSC markers after being in space. NSCs displayed both higher oxygen consumption and glycolysis than ground controls. These cells also kept their ability to become young neurons. Electrophysiological recordings of space NSC-derived neurons showed immature cell membrane properties characterized by small capacitance and very high input resistance. Current injections elicited only an incipient action potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 11 publications
(16 reference statements)
4
9
0
Order By: Relevance
“…Previously, we demonstrated that, just like in simulated microgravity, space microgravity (SPC-µG) induces enhanced proliferation of NSCs. We corroborated this during space flight [3] and confirmed that NSCs proliferated more than ground controls after space flight [4]. We also found that the vast majority of these cells adapted to Earth's gravity and displayed typical features of NSCs, such as self-renewal via normal proliferation, where cytokinesis occurred within the range of ground control cells without significant differences [4].…”
Section: Introductionsupporting
confidence: 75%
“…Previously, we demonstrated that, just like in simulated microgravity, space microgravity (SPC-µG) induces enhanced proliferation of NSCs. We corroborated this during space flight [3] and confirmed that NSCs proliferated more than ground controls after space flight [4]. We also found that the vast majority of these cells adapted to Earth's gravity and displayed typical features of NSCs, such as self-renewal via normal proliferation, where cytokinesis occurred within the range of ground control cells without significant differences [4].…”
Section: Introductionsupporting
confidence: 75%
“…In addition, the cells revealed higher oxygen consumption and glycolysis compared with ground controls. These cells also kept their ability to become young neurons [53]. This was further corroborated in another study, which revealed that human neural stem cells proliferated seven times more in space in comparison to ground based controls [54].…”
Section: Gut Microbiome Angiogenesis and Link With Visual Impairmentsupporting
confidence: 60%
“…This study suggested that there may be weakening of the interior and exterior cellular structures of the retinal cells in a simulated microgravity environment, which might affect the function of the retinal layer. Nonetheless, it was recently reported that human neural stem cells proliferate when in space and express specific markers [53]. Neural stem cells are integral in the maintenance of the central nervous system's function.…”
Section: Gut Microbiome Angiogenesis and Link With Visual Impairmentmentioning
confidence: 99%
“…We have previously reported that sim-µG increased the proliferation of rodent and human OLPs with the concomitant shortening of the cell cycle [ 18 ]. We have also reported that sim-µG enhances OLPs’ mitochondrial function and lipid metabolism [ 18 ] and that NSCs proliferate more while in space and after space flight [ 19 , 20 ]. These findings led us to hypothesize that space microgravity would produce similar results with regard to OLPs.…”
Section: Introductionmentioning
confidence: 99%